Design And Study Of Domestic Cooling System Through Roof Ventilation Assisted By Evaporative Cooling - Chai, Yik Zhien (Universiti Sains Malaysia, 2019)
Climate of Malaysia is hot. It causes high indoor temperature in the building. Roof is the part which absorbs huge amount of heat flux in a building. To reduce the heat transferred from the roof, roof ventilation is needed. There are many existing roof ventilation methods but they have their disadvantages such as less efficient and much energy loss. In this project, domestic cooling system through roof ventilation assisted by evaporative cooling is designed. The performance of designed domestic cooling system is investigated through experiment and simulation. Domestic cooling system through roof ventilation assisted by evaporative cooling combines the theories of natural ventilation, forced ventilation and direct evaporative cooling. By using this method, the energy used for the cooling system can be reduced. Design, fabrication, experiment and simulation are done in this project. For design part, an actual size model and a prototype model are designed. For fabrication part, the prototype model is fabricated and used for doing experiment. For experiment part, two types of experiment are involved in this project. First type of experiment is carried out to measure the efficiency of the cooling system. Second type of experiment is carried out to measure the performance of the cooling system with different air speed in cooling duct. Simulation is done to compare the performance of cooling system between the prototype design and the actual size design in different conditions. Simulation results is also compared with experimental results. The experimental results show that the cooling system with 4m/s air speed has the highest cooling efficiency, which is 49.3%. The best performance of the roof ventilation assisted by evaporative cooling system can reduce 10.58oC. The temperature difference between the simulation result and experimental result is only 0.26oC, it is still acceptable. Thus, domestic cooling system through roof ventilation assisted by evaporative cooling can be known as an efficient cooling system.